PENGARUH PENERAPAN MODEL PROJECT BASED LEARNING TERHADAP KEMAMPUAN MENYELESAIKAN SOAL HOTS MATEMATIS SISWA - Pika Audia Sari; Dwi Yulita; Tiara Nurayuwati; Virlizha Ananda Putri; Netriwati (Universitas Teknokrat Indonesia, 2026)
This study aims to analyze the effect of implementing the Project Based Learning (PjBL) model on students' ability to solve Higher Order Thinking Skills (HOTS) mathematical problems at SMP Tunas Dharma. The background of this study is based on the importance of higher-order thinking skills in mathematics learning and the need for instructional models that can enhance these skills. The novelty of this research lies in the implementation of the Project Based Learning (PjBL) model to improve students' ability to solve HOTS mathematical problems in basic statistics at the junior high school level, which is examined through HOTS test results and students' responses to the learning process. This study employed a quantitative approach with an experimental design. The research subjects consisted of two classes: an experimental class that received instruction using the Project Based Learning (PjBL) model and a control class that received conventional learning. The study was conducted through several stages, namely the administration of a pre-test, the implementation of Project Based Learning (PjBL) in the experimental class and conventional learning in the control class, and the administration of a post-test to measure students' HOTS mathematical abilities after the treatment. The research instrument was a HOTS mathematical ability test that had been validated and tested for reliability. Data analysis techniques included validity and reliability tests, normality tests, homogeneity tests, descriptive statistical analysis, and the Independent Samples t-test to determine differences in HOTS mathematical abilities between the two research groups. The results showed that the data were normally distributed and homogeneous. Based on the results of the Independent Samples t-test, a significance value of p < 0.05 was obtained, indicating a significant difference between the experimental and control groups. Therefore, it can be concluded that the implementation of the Project Based Learning (PjBL) model has a significant effect on students' ability to solve HOTS mathematical problems.